KONSEP MANUSIA SEBAGAI AL-BASYAR DALAM AL-QUR’AN - Imroatus Sholikha Azzuhriyyah; Achmad Khudori Soleh (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2023)
Abstract Al-basyar is one of the terms in the Qur'an in a physical context to refer to humans. Humans are objects whose existence can be directly observed by the five senses, have a physical image or a real form and a solid form. The purpose of writing the article is to analyze the human context as al-basyar in the Qur'an. The method used in this study is a qualitative research method with a library research approach in which the data sources come from integrated libraries, books and journals. The results of this study state that (1) The concept of human as al-basyar in the Qur'an shows that humans are biological creatures that can be physically seen by the eye (physical). (2) The word al-Basyar consists of the letters ba, syin and ra which in language mean human physicality, mentioned 36 times spread across 23 letters in the Koran with different meanings and variations of writing. (3) Prophets are humans who are the same as humans in general, but different from humans in general because they have several advantages given by Allah as a differentiator from ordinary humans. Keywords : Al-Basyar, Perspective of the Qur'an, Basic Human Needs, Prophethood